Maghreb Economic Integration between Success Opportunities and Activation Constraints - Benkhedidja, Mouncif; Harireche, Nadji (Milev Journal of Research and Studies, 2018)
Abstract: This paper addresses the subject of Maghreb economic integration and the range of opportunities offered by the real Maghreb countries integration, because the region countries have economic, natural, human and cultural assets that guarantee an economic and political unit formation with an important weight in the global economic system. Through this study we aim to present and analyze the Maghreb experience in regional economic integration and the main reasons that prevented the real embodiment of the project, as well as the analysis of the possible opportunities and gains by the integration of concerned countries, and the priorities through which those opportunities could be seized, drawing on most important international organizations statistics and scenarios. One of the most important results of this study is that Maghreb economic integration promotes intra-regional trade development in order to strengthen its international bargaining position and uniting its efforts to meet common challenges in the area, making it more attractive to domestic and foreign investments, it is therefore an irreplaceable strategic choice to ensure prosperity and prosperity.